Grammatical Errors On Social Media - Angela M.Sihotang; Friskila Sitanggang; Novitriani Hasugian; Fachri Yunanda (Jurnal Indonesia Sosial Teknologi, 2021)
This article discusses grammatical error in social media post. The objectives are to investigate the types of common errors by social media users. By describing the dominant errors and also elaborate on the reason why social media users did the errors on their posts. The design of this research was descriptive qualitative the subject of this study consisted of 30 akum social media users, 15 from facebook and 15 from instagram. Author make social media as a samples. Findings show that there were some types of errors such as ommision 10 (33,3%), addition 4 (13,3%), misordering 7 (23,3%), misformation 9 (30%). Thus ommision is the dominant type found. Errors occur because social media users do not understand the structure of language and writing English correctly. in addition, users often make errors in their post, sometimes only as a style and aiming for rumors but without realizing it causes fatal irregularities. A part from that the curiosity of social media users in understanding English is still lacking.